Sustainable Urban Revitalization Approach to Old City Centers: An Analytical Review of Al-Dahou District in Riyadh - Al-Otaibi, خالد عايض; Alzamil, وليد (Journal of King Abdulaziz University: Environmental Design Sciences, 2026)
This paper aims to review the urban revitalization approach for historic city centers based on a case analysis of the Al-Dahou neighborhood in Riyadh, a heritage neighborhood that has witnessed a large-scale urban development project. The study used a descriptive and qualitative approach, including a review of previous studies, field interviews, and an analysis of official reports. The Al-Dahou neighborhood revitalization project was evaluated according to four main dimensions: cultural, economic, urban, and social. The results showed that the project succeeded in its urban and cultural aspects, particularly through the use of heritage architectural elements that reflected local identity. It also contributed to stimulating the local economy through investment activities of a cultural nature. However, the study revealed challenges in activating the social dimension, as the local community was not sufficiently involved in the planning, implementation and evaluation stages. The study recommends adopting an integrated vision based on community engagement and strengthening cultural identity.